Nigral proteasome inhibition in mice leads to motor and non-motor deficits and increased expression of Ser129 phosphorylated α-synuclein - Bentea, Eduard; Van der Perren, Anke; Van Liefferinge, Joeri; El Arfani, Anissa; Albertini, Giulia; Demuyser, Thomas; Merckx, Ellen; Michotte, Yvette; Smolders, Ilse; Baekelandt, Veerle; Massie, Ann (Frontiers in Behavioral Neuroscience, 2015)
Parkinson’s disease is a neurodegenerative disorder characterized by motor and non-motor disturbances. Various pathogenic pathways drive disease progression including oxidative stress, mitochondrial dysfunction, α-synuclein aggregation and impairment of protein degradation systems. Dysfunction of the ubiquitin-proteasome system in the substantia nigra of Parkinson’s disease patients is believed to be one of the causes of protein aggregation and cell death associated with this disorder. Lactacystin, a potent inhibitor of the proteasome, was previously delivered to the nigrostriatal pathway of rodents to model nigrostriatal degeneration. Although lactacystin-treated animals develop parkinsonian motor impairment, it is currently unknown whether they also develop non-motor symptoms characteristic of this disorder. In order to further describe the proteasome inhibition model of Parkinson’s disease, we characterized the unilateral lactacystin model, performed by stereotaxic injection of the toxin in the substantia nigra of mice. We studied the degree of neurodegeneration and the behavioral phenotype one and three weeks after lactacystin lesion both in terms of motor impairment, as well as non-motor symptoms. We report that unilateral administration of 3 µg lactacystin to the substantia nigra of mice leads to partial (~40%) dopaminergic cell loss and concurrent striatal dopamine depletion, accompanied by increased expression of Ser129-phosphorylated α-synuclein. Behavioral characterization of the model revealed parkinsonian motor impairment, as well as signs of non-motor disturbances resembling early stage Parkinson’s disease including sensitive and somatosensory deficits, anxiety-like behavior, and perseverative behavior. The consistent finding of good face validity, together with relevant construct validity, warrant a further evaluation of proteasome inhibition models of Parkinson’s disease in pre-clinical research and validation of therapeutic targets.